2014
DOI: 10.1002/jcph.368
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of self‐reported drug ingestion histories in emergency department patients

Abstract: Inaccuracies in self-reports may lead to duplication of therapy, failure to appreciate non-compliance leading to exacerbation of chronic medical conditions, or inaccurate research conclusions. Our objective is to determine the accuracy of self-reported drug ingestion histories in patients presenting to an urban academic emergency department (ED). We conducted a prospective cohort study in ED patients presenting for pain or nausea. We obtained a structured drug ingestion history including all prescription drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Accuracy of data is limited to honesty of patient reporting. This is known to be problematic in terms of important variables such as illicit drug use, analgesic consumption, and presence of mental health conditions (Monte, Heard, Hoppe, Vasiliou, & Gonzalez, 2015). We cannot exclude the possibility that some patients in the study had drug-seeking behavior, which could influence pain satisfaction scores.…”
Section: Limitationsmentioning
confidence: 95%
“…Accuracy of data is limited to honesty of patient reporting. This is known to be problematic in terms of important variables such as illicit drug use, analgesic consumption, and presence of mental health conditions (Monte, Heard, Hoppe, Vasiliou, & Gonzalez, 2015). We cannot exclude the possibility that some patients in the study had drug-seeking behavior, which could influence pain satisfaction scores.…”
Section: Limitationsmentioning
confidence: 95%
“…Urine toxicology can be used to verify a patient's self-reported drug ingestion history (53). However, urine toxicology of patients on long-term OPRs is not a reliable strategy for identifying opioid addiction.…”
Section: Secondary Preventionmentioning
confidence: 99%
“…2 It is possible that reporting bias in the era after legalization has confounded these findings; however, we previously found that the reporting on marijuana use among Colorado residents during the medical marijuana period was reliable. 3 …”
Section: To the Editormentioning
confidence: 99%